Meta-Analysis: The Effect of Assessment Types on Learning Outcomes in Islamic Religious Education - Boy, La; Wahyuni, Imelda (Dirasah: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the effects of various forms of assessment on learning outcomes in Islamic Religious Education (IRE) through a meta-analysis approach. IRE learning outcomes are understood as integrated learning achievements encompassing the cognitive, affective, and psychomotor domains. The meta-analysis was conducted on 15 quantitative research articles published between 2018 and 2025 that met the inclusion criteria, including experimental, quasi-experimental, and correlational designs. Effect sizes were calculated using Cohen’s d and Hedges’ g to determine the magnitude of the impact of each assessment type on IRE learning outcomes. The results indicate that, overall, assessment types have a positive effect on IRE learning outcomes, with an average effect size of 0.546, which falls within the moderate effect category. Formative assessment based on feedback and performance-based assessment demonstrate the strongest effects, classified as large effect sizes, whereas conventional cognitive assessments such as quizzes and homework assignments show relatively small effects. Based on educational level, the impact of assessment on IRE learning outcomes is most significant at the senior high school (SMA/MA) level compared to elementary (SD/MI) and junior high school (SMP/MTs) levels. These findings underscore that the effectiveness of assessment is largely determined by its alignment with the holistic objectives of Islamic Religious Education. Therefore, this study recommends strengthening the implementation of authentic, reflective, and formative assessments in Islamic Religious Education learning.